2022
DOI: 10.1177/10600280211073321
|View full text |Cite
|
Sign up to set email alerts
|

Weight Changes With Integrase Strand Transfer Inhibitor Therapy in the Management of HIV Infection: A Systematic Review

Abstract: Objective: To describe weight changes with integrase strand transfer inhibitor (INSTI) therapy. Data Sources: A literature search was performed (through December 15, 2021) using the PubMed and CINAHL databases using the search terms: “integrase inhibitors,” “integrase strand transfer inhibitors,” and “weight.” Study Selection and Data Extraction: Studies were included that provided relevant information on weight or body mass index (BMI) changes on INSTI therapy. Controlled or observational studies comparing di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 121 publications
1
6
0
Order By: Relevance
“…However, as the prevalence of obesity in PLWH continues to increase, further investigation into other weight gain mechanisms is necessary. 33,36 Importantly, no included studies reported on the development of metabolic syndrome, diabetes or cardiovascular complications. In addition to reporting on weight changes, future research should investigate these clinically important outcomes Of note, one study of patients switching from EVG/F/ TAF to B/F/TAF found a significant decrease in eGFR of 5 mL/min.…”
Section: Discussionmentioning
confidence: 99%
“…However, as the prevalence of obesity in PLWH continues to increase, further investigation into other weight gain mechanisms is necessary. 33,36 Importantly, no included studies reported on the development of metabolic syndrome, diabetes or cardiovascular complications. In addition to reporting on weight changes, future research should investigate these clinically important outcomes Of note, one study of patients switching from EVG/F/ TAF to B/F/TAF found a significant decrease in eGFR of 5 mL/min.…”
Section: Discussionmentioning
confidence: 99%
“…Our study was not suited to evaluate associations between incident hypertension and ART (95% of our participants were on the same dolutegravir-based regimen–TLD), however some studies in SSA have found an association between older NRTI, NNRTI and PI agents (namely zidovudine, stavudine, nevirapine, and lopinavir-ritonavir) and hypertension [ 28 , 29 ]. Moreover, the increasingly recognized associations between integrase inhibitors and obesity and other metabolic complications is of concern [ 37 , 38 ], as these conditions tend to predispose invidiuals to hypertension and atherosclerotic cardiovascular (ASCVD) disease possibly increasing cardiovascular-related morbidity and mortality. As > 90% of all PWH in SSA are currently on an integrase based regimen (including participants in our sample), and as HIV is a known independent risk factor for ASCVD-related events, this may be problematic [ 39 – 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that INSTIs may be associated with weight gain. 45 At Week 96 in HPTN 083 and HPTN 084, those who received CAB-LA had gained a median of 2.1 and 4 kg, respectively, compared with 1 and 3 kg, respectively, for those who received FTC/TDF. 43,44 The clinical significance of this weight gain is unclear, and there is less data with CAB-LA compared with other…”
Section: Cab-lamentioning
confidence: 96%
“…Other than ISRs, CAB‐LA appears to be well‐tolerated. There is increasing evidence that INSTIs may be associated with weight gain 45 . At Week 96 in HPTN 083 and HPTN 084, those who received CAB‐LA had gained a median of 2.1 and 4 kg, respectively, compared with 1 and 3 kg, respectively, for those who received FTC/TDF 43,44 .…”
Section: Pre‐exposure Prophylaxismentioning
confidence: 99%